A prospective observational study of foetal outcome in twin pregnancy delivering at a tertiary health care center of South Gujarat - Jariwala, Heny K.; Patel, Falguni B.; Chaudhari, Minal R.; Shrivastava, Anjani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Worldwide increased incidence of twin gestation. The rates of twin gestation have a direct effect on the rates of preterm birth and its co-morbidities. Importantly, this increased risk applies to each fetus and is not simply the result of more foetuses. Methods: This prospective study was carried out in department of obstetrics and gynaecology. 100 consecutive subjects fulfilling inclusion criteria admitted to labour room and obstetrics intensive care enrolled over a period of around 1 year. Results: In this study twin delivery accounted for 1.3% of all delivery at our institute. On analysing neonatal morbidities Prematurity was commonest 65%, VLBW (23% first twin, 30% second twin), RDS (9% first twin, 13% second twin), birth asphyxia (7% first twin, 12% second twin), neonatal hyperbilirubinemia (7% first twin, 8% second twin). 34% of first twin and 40% of second twin required NICU admission. Early neonatal death observed in 6% of first twin and 8% of second twin. It was observed that proportion of neonatal complications was more in MCDA as compared to DCDA and in un-booked subjects as compared to booked subjects. This difference is statistically significant among both twin (p value<0.05). Conclusions: Twin pregnancy is associated with high perinatal morbidity. Specialized obstetrics and Intensive Neonatal care can decrease neonatal morbidity and mortality in twin gestation. We need to be extra vigilant in monochorionic twins and twin pregnancy with inadequate antenatal care.